Pengembangan Aplikasi Perangkat Bergerak Rekomendasi Tempat Latihan Beladiri di Malang dengan GDSS dan LBS Berbasis Android - Djohansyah Putra; Ratih Kartika Dewi; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Martial arts are a method by which individuals can protect themselves from increased danger. There are several types of martial arts in Indonesia, both original Indonesian martial arts, namely pencak silat or various important martial arts from other countries such as karate, judo, taekwondo, and capoeira. Martial arts venues in Malang are scattered in several districts, along with the times of the type of martial arts are also increasingly diverse. With so many types and places of martial arts, it arises for people who want to practice to choose a martial arts place in accordance with their wishes. Application recommendations for martial arts practice sites have been built on previous research, but only for single users, whereas in reality the selection of martial arts practice sites is sometimes done not alone and done in groups. So we need an Android-based mobile application that can recommend martial arts practice sites in Malang that are in accordance with user criteria and are done in groups. Application recommendation for martial arts practice sites in Malang is designed with an Android-based Group Decision Support System and Location Based Services using TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) and Borda algorithms with criteria in the form of distance between users and martial arts practice sites, training costs in one month, and the amount of exercise time in one week. The results of testing the application using Blackbox are worth 100% and the functionality is declared valid. Other tests conducted are algorithm validation testing, where testing is done by comparing the outputs of the system with manual calculations. The results of the application output and manual calculations are 100%, and usability testing, where testing is done to determine the quality of the software interface. The application usability test results got a value of 73.5 indicating a Good rating for the adjective rating and grade B- on percentile rank, so it is stated that the application can be accepted by the user.